2018
DOI: 10.1007/978-3-319-91473-2_29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fuzzy Integral-Fuzzy Measure Based Ensemble Algorithms with the State-of-the-Art Ensemble Algorithms

Abstract: Abstract. The Fuzzy Integral (FI) is a non-linear aggregation operator which enables the fusion of information from multiple sources in respect to a Fuzzy Measure (FM) which captures the worth of both the individual sources and all their possible combinations. Based on the expected potential of non-linear aggregation offered by the FI, its application to decision-level fusion in ensemble classifiers, i.e. to fuse multiple classifiers outputs towards one superior decision level output, has recently been explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Ensemble Classification determines the class to which a new object belongs by integrating the results of multiple classifiers. In the previous studies [1], [6], [15], the researchers concluded that aggregation operator based ensemble classifiers worked well in a number of applications such as multi-criteria decision making (MCDM) [16], forensic science [17], software defect prediction [18], brain computer interface (BCI) [19], computer vision [20], [21] and explosive hazard detection [22]. Here, we use the application of ensemble classification to compare the a priori measure with the Sugeno λ-measure and the Uriz measure.…”
Section: Ensemble Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ensemble Classification determines the class to which a new object belongs by integrating the results of multiple classifiers. In the previous studies [1], [6], [15], the researchers concluded that aggregation operator based ensemble classifiers worked well in a number of applications such as multi-criteria decision making (MCDM) [16], forensic science [17], software defect prediction [18], brain computer interface (BCI) [19], computer vision [20], [21] and explosive hazard detection [22]. Here, we use the application of ensemble classification to compare the a priori measure with the Sugeno λ-measure and the Uriz measure.…”
Section: Ensemble Classificationmentioning
confidence: 99%
“…Majority Voting with SVM (MJSVM): Let x be an instance and S i (i = 1, 2, ..., k) Support Vector Machine (SVM) classifiers that output class labels m i (x, c j ). For each class label c j (where j = 1, ..., n) [15], the output of the final classifier y(x) for instance x is given by:…”
Section: Ensemble Classificationmentioning
confidence: 99%
See 1 more Smart Citation